Lmx1b Is Required for Maintenance of Central Serotonergic Neurons and Mice Lacking Central Serotonergic System Exhibit Normal Locomotor Activity - Zhao, Zhong-Qiu (J Neurosci, 2006)
Central serotonergic neurons have been implicated in numerous animal behaviors and psychiatric disorders, but the molecular mechanisms underlying their development are not well understood. Here we generated Lmx1b (LIM homeobox transcription factor 1 β) conditional knock-out mice (Lmx1b(f/f/p)) in which Lmx1b was only deleted in Pet1 (pheochromocytoma 12 ETS factor-1)-expressing 5-HT neurons. In Lmx1b(f/f/p) mice, the initial generation of central 5-HT neurons appeared normal. However, the expression of both 5-HT-specific and non-5-HT-specific markers was lost in these neurons at later stages of development. The loss of gene expression is concomitant with downregulation of Lmx1b expression, with the exception of serotonin transporter Sert and tryptophan hydroxylase TPH2, whose expression appears to be most sensitive to Lmx1b. Interestingly, the expression of Pet1 is tightly coupled with expression of Lmx1b during later stages of embryonic development, indicating that Lmx1b maintains Pet1 expression. In Lmx1b(f/f/p) mice, almost all central 5-HT neurons failed to survive. Surprisingly, Lmx1b(f/f/p) mice survived to adulthood and exhibited normal locomotor activity. These data reveal a critical role of Lmx1b in maintaining the differentiated status of 5-HT neurons. Lmx1b(f/f/p) mice with normal locomotor function should provide a unique animal model for examining the roles of central 5-HT in a variety of animal behaviors.